Pemetaan Kualitas Laporan Keuangan Pemerintah Daerah di Kawasan Timur Jawa Timur Berbasis Sistem Informasi Geografi - Taufik Kurrohman (Universitas Jember, 2010)
Local government financial reports (LGFR) is an information which contains data about the wealth of economic activity results from a government within a single budget period. Results from the recording of those statements is a description of achievements in the framework of public finance management. This study aimed to identify areas of financial management performance based on the identification of opinions, findings, and recommendations given by the BPK RI on examination of the financial statements of local districts and cities in “East area” in East Java Province from 2006 until the 2008 budget yearusing GIS. The results showed a fluctuating performance towards achievement of the opinions, findings, and recommendations of the examination results of local government financial reports on each district and town in “East area” in East Java. This is demonstrated by comparing the achievement opinions, findings, and recommendations among the counties and cities during the three-year budget. Keywords: LKPD, Opinion, Findings.